Gene-wide characterization of common quantitative trait loci for ABCB1 mRNA expression in normal liver tissues in the Chinese population. - Weihua Shou (Public Library of Science (PLoS), 2012)
In order to comprehensively screen genetic variants leading to differential expression of the important human ABCB1 gene in the primary drug-metabolizing organ, ABCB1 mRNA expression levels were measured in 73 normal liver tissue samples from Chinese subjects. A set of Tag SNPs. were genotyped. In addition, imputation was performed within a 500 kb region around the ABCB1 gene using the reference panels of 1,000 Genome project and HapMap III. Bayesian regression was used to assess the strength of associations by compute Bayes Factors for imputed SNPs. Through imputation and linkage disequilibrium analysis, the imputed loci rs28373093, rs1002205, rs1029421, rs2285647, and rs10235835, may represent independent and strong association signals. rs28373093, a polymorphism 1.5 kb upstream from the ABCB1 transcription start site, has the strongest association. 2677 G>A/T and 3435C>T confer a clear gene-dosage effect on ABCB1 mRNA expression. The systematic characterization of gene-wide common quantitative trait loci associated with ABCB1 mRNA expression in normal liver tissues would provide the candidate markers to ABCB1-relevant clinical phenotypes in Chinese population.